Theoretical and applied aspects of relations and operations for sequences of time intervals - Kudym, K.A.; Reznichenko, V.A.; Proskudina, G.Yu.; Ovdii, О.М. (PROBLEMS IN PROGRAMMING, 2025)
Prombles in programming 2013; 3: 61-68